Education NGOs in Makhanda, South Africa: A Zero Sum of Philanthropy and Survival - Nomsenge, Sinazo Onela (Africanus: Journal of Development Studies, 2019)
Thought and commentary surrounding the upsurge of non-governmental organisations (NGOs) and their involvement in the design and implementation of development in the Global South are accompanied by an unrelenting set of contradictions and self-replicating inconsistencies. These are often embedded in the sector’s nomenclature, ideological underpinnings, intent and impact. Opposing bands of scholarship have sustained these tensions by securing NGOs both within the ambit of developmental thought and practice and also within the criticisms waged against western domination and its splinter models of modernity. In an attempt to extend these prevailing annotations, this paper holds the idealisation of NGOs up to scrutinous reflection within the context of Makhanda’s inequitable educational landscape by proposing that, in order to balance organisational uncertainties with the socio-economic urgencies upon which they trade, NGOs sustain several and, at times, competing affiliations all of which are central to organisational preservation and legitimacy. The tactical means by which organisations preserve these allegiances often deputise socio-economic and educational overhaul in favour of survival. Therefore, this article lays out the ways in which organisational urgencies intersect with contextually specific needs of reform in what becomes a zero sum of philanthropy and survival; this to the extent that, in large part, NGO interventions often serve to moderate, rather than uproot, the set of socio-economic features for which non-state intervention continues to be hailed and hallowed.